The Impact of National Cultural Distance on Foreign Direct Investment in Iraq (Global Journal of Management and Business Research, 2014)
Political and security risks coupled with cultural distance have profound effects on foreign investments by multi-national enterprises. A qualitative case study was conducted to investigate the impact of cultural distance on foreign direct investment in the heterogeneous and postconflict country of Iraq. Data were collected from interviews with 15 business and government subject matter experts, and from a review of publically available documents. The findings showed majority of foreign investment was from Arab countries and Iraq#x2019;s neighbors. There was limited investment by Western firms in Iraq, outside its oil and gas sector, and those taking place were mainly in the housing construction market. Kurdistan region attracted significant investment activities. Wholly-owned and joint ventures characterized mode of entry by MNEs. Substantial number of investment licenses issued did not materialize due to hurdles brought about by government agencies. Statistical data regarding the real dollar amount of foreign investment in Iraq are still lacking. The findings showed an important role played by Iraqi expatriates as facilitators of foreign investment. Implications to other post conflict and heterogeneous countries are presented and recommendations made.
Keywords: foreign direct investment; iraq; post-conflict country; cultural distance; decision making; multinational enterprises; international business